Artificial Intelligence (AI) in Academic Libraries in Ghana: a Case Study of Three Academic Libraries - OWUSU-ANSAH, CHRISTOPHER; Yeboah , Patience; Amoako, Kwabena; Boateng, Michael Sakyi; Nutsukpui, Erica; Amankwah, Angelina (International Journal of Knowledge Content Development & Technology, 2025)
The study aimed to investigate the implementation of artificial intelligence (AI) initiatives in three academic libraries in the Kumasi Metropolis of Ghana. The objectives of the study were to identify specific AI initiatives in the selected academic libraries; analyze the impact of AI initiatives on user experiences in the selected academic libraries; explore challenges associated with the implementation of AI initiatives in the selected libraries; and investigate the strategies and approaches employed by academic libraries to address challenges related to AI initiatives. The study applied survey research methods to provide insights into the benefits, challenges, and potential long-term implications of integrating AI technologies in university libraries. The study’s population consists of library staff from three (3) universities in the Ashanti Region of Ghana: Akenten Appiah-Menka University of Skills Training and Entrepreneurial Development, Kwame Nkrumah University of Science and Technology, and Christian Service University College. The data were analyzed using the Statistical Package for Social Sciences (SPSS) tool. The study found that AI adoption in the selected academic libraries as generally moderate. Among others, the study recommends prioritizing a strategic integration of AI applications in academic libraries in Ghana. The study explores the pervasiveness of Artificial Intelligence initiatives in resource-constrained academic libraries in a global south country.